Vibration control for fine motion flexible robot arm using proportional integral derivative (PID) controller / Mohd Hafizi Omar - Omar, Mohd Hafizi (2019)
In this paper, the three term controller also known as Proportional Integral Derivative (PID) controller was proposed to control the most common problem on flexible robot arm which is vibration control problem. The controller description and properties included to support the relation with the vibration problem of flexible robot arm. MATLAB is used for system identification to validate estimation by comparing model response and measured response from the independent data. Estimation method is used to estimate the parameters of the selected model structure thus evaluate the estimated model so that it meet the requirement for the robot arm. In this project, transfer function method have been use to calculate model response so that it almost equal with the measured response properties. For tuning of PID controller, the trial and error method have been used where the value of Integral term (Ki), Derivative term (Kd) and Proportional term (Kp) was adjusted so that it adequate to reduce the model response. For model design with controller and simulation of the system, Simulink is used for the purposes.